Development of Model Culinary Center Design Based on Customers Wants in Surabaya Study Object: Culinary Center “Gunung Anyar” Surabaya - Siti Azizah (Nusantara Science and Technology Proceedings)
Street vendors in urban areas are one solution to reduce unemployment and reduce poverty, so it must be completed properly. To overcome the problem of street vendors especially culinary vendors, Surabaya City Government has a policy to relocate the culinary street vendors from inappropriate to the Center of Culinary. Until now many culinary centers are built in several locations in Surabaya and it will increase because the culinary center is the optimal solution for the problem of street vendors in Surabaya. The fact at the moment, there are some culinary centers are full by customers but there is also a quiet. If a Culinary Center out of business then it is feared that the street vendors will comeback to old locations and the city's problems to street vendors will happen again. For that we need to know the aspects that cool customers to the design Culinary center So that can be developed Culinary center arrangement is representative for the sustainability of business street vendors in it. The Aspects to be studied are aspects of form, space, outer space arrangement and supporting activities from several culinary centers in Surabaya. The research is qualitative research with Research and Development method. Data handling is done quantitatively. Research in the form of identification of design aspects that affect the sustainability of street vendor business in terms of user desires so that subsequently can be generated the development of culinary design center model by taking the object of study culinary center of Gunung Anyar, Surabaya, Indonesia.